De Garengeot’s Hernia: Report of a Rare Surgical Emergency and Review of the Literature - Misiakos, Evangelos P.; Paspala, Anna; Prodromidou, Anastasia; Machairas, Nikolaos; Domi, Vasileia; Koliakos, Nikolaos; Karatzas, Theodore; Zavras, Nick; Machairas, Anastasios (Frontiers in Surgery, 2018)
This is a report of a case who was admitted and operated on for a strangulated femoral hernia. The hernia sac contained a gangrenous appendix, which was excised and the hernia was repaired with sutures without complication. De Garengeot's hernia, although very rare, should be included in the differential diagnosis of cases with strangulated hernia and should receive the optimal treatment.